Holocene climate change influences on trace metal and organic matter geochemistry in the sediments of an Arctic lake over 7, 000 years. (March 2017) - Outridge, P.M.; Sanei, H.; Courtney Mustaphi, C.J.; Gajewski, K.
Abstract: This study employed a 6.48 m long dated sediment core to characterize the amount of variation in background trace metal concentrations, and develop an understanding of the role of climatic influences on sediment inorganic and organic geochemistry in a High Arctic lake over ∼7000 years of the Holocene. Element geochemistry reflected varying detrital contributions from two geological sources within the catchment: carbonates (dolomites and limestones) which provided the dominant major element by weight (i.e., Ca), and carbonaceous mudrocks (primarily shales) which may have contributed most of the other trace and minor elements. The presence of eroded shale-hosted organic matter (OM) in sediments was confirmed by reflectance measurements on reworked vitrinitic macerals which had similar values to Palaeozoic carbonaceous rocks in the watershed. Bimodal distribution of the reflectance data suggested that two sources of vitrinitic macerals were present, from different formations. Variable dilution of shale-sourced elements by carbonates, related to climate (temperature)-influenced rates of dissolution and erosion, was the dominant process controlling inorganic geochemical composition. RockEval pyrolysis of bulk sediment OM revealed the unusual finding of two distinct sources of sediment kerogen which alternated in importance during the Holocene: a "baseline" state of eroded shale-hosted OM which was probably always present but which dominated sediment OM when autochthonous (algal) production was minimal, and an "enhanced algal state" which dominated when limnological conditions favored higher autochthonous productivity. Periods with more frequent examples of the enhanced algal state occurred during the mid- and late-Holocene, coincident with periods of relatively high summer air temperatures in the region. This study provides evidence that climate, particularly air temperature, influenced sediment inorganic and organic geochemical compositions in this lake through its effect on catchment geology erosion rates and aquatic primary productivity. It shows the value of studying very long periods of sediment accumulation as a background context for recent sediment metal concentrations. Highlights: Inorganic and organic geochemistry of a High Arctic lake sediment strongly affected by climate change over 7000 years. Element concentrations controlled by changing inputs from catchment shales, diluted by carbonates. Inputs of carbonates correlated with summer air temperature, possibly because of its effect on carbonate dissolution rates. Sediment organic matter from ancient shales and autochthonous primary productivity, the latter dominating during warmer periods. Short cores representative of background concentrations of Hg, Pb & Cd, but long cores important for understanding sedimentary processes.